The Impact of Vocational Schooling on Human Capital Development in Developing Countries : Evidence from China - Loyalka, Prashant; Huang, Xiaoting; Zhang, Linxiu; Wei, Jianguo; Yi, Hongmei; Song, Yingquan; Shi, Yaojiang; Chu, James (World Bank, Washington, DC, 2015)
A number of developing countries are currently promoting vocational education and training (VET) as a way to build human capital and strengthen economic growth. The primary aim of this study is to understand whether VET at the high school level contributes to human capital development in one of those countries—China. To fulfill this aim, a longitudinal data on more than 10,000 students in vocational high school (in the most popular major, computing) and academic high school from two provinces of China are used. First, estimates from instrumental variables and matching analyses show that attending vocational high school (relative to academic high school) substantially reduces math skills and does not improve computing skills. Second, heterogeneous effect estimates also show that attending vocational high school increases dropout, especially among disadvantaged (low-income or low-ability) students. Third, vertically scaled (equated) baseline and follow-up test scores are used to measure gains in math and computing skills among the students. The results show that students who attend vocational high school experience absolute reductions in math skills. Taken together, the findings suggest that the rapid expansion of vocational schooling as a substitute for academic schooling can have detrimental consequences for building human capital in developing countries such as China.